f(x)=In(9-3x)(4+6x)

Simple and best practice solution for f(x)=In(9-3x)(4+6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=In(9-3x)(4+6x) equation:


Simplifying
f(x) = In(9 + -3x)(4 + 6x)

Multiply f * x
fx = In(9 + -3x)(4 + 6x)

Multiply (9 + -3x) * (4 + 6x)
fx = nI(9(4 + 6x) + -3x * (4 + 6x))
fx = nI((4 * 9 + 6x * 9) + -3x * (4 + 6x))
fx = nI((36 + 54x) + -3x * (4 + 6x))
fx = nI(36 + 54x + (4 * -3x + 6x * -3x))
fx = nI(36 + 54x + (-12x + -18x2))

Combine like terms: 54x + -12x = 42x
fx = nI(36 + 42x + -18x2)
fx = (36 * nI + 42x * nI + -18x2 * nI)
fx = (36nI + 42nxI + -18nx2I)

Solving
fx = 36nI + 42nxI + -18nx2I

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = 36nx-1I + 42nI + -18nxI

Simplifying
f = 36nx-1I + 42nI + -18nxI

Reorder the terms:
f = 42nI + 36nx-1I + -18nxI

See similar equations:

| Msquared-5=59 | | .16-.01(x+2)=-0.02(2-x) | | 3xy(5xy)+3xy(1)=equation | | 17x-3-12=.2(25x-10) | | 3xy(5xy)+3xy(1)= | | 16t^2+150t+20=0 | | 5x+2=36 | | .5x-.625=.75x+.375 | | 2x(x-4)+x(3-2x)= | | 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 |

Equations solver categories